Answer:
c = -6
d = 2
Step-by-step explanation:
After reflection about the x-axis:
A --> A'
(x,y) --> (x,-y)
(2,3) --> (2,-3)
(4,3) --> (4,-3)
(2,6) --> (2,-6)
After translation:
(2 + c, -6 + d) --> (-4, -4)
2+c = -4
c = -6
-6+d = -4
d = 2
6 + 12 = 18
18/9 = 2
The answer is 2
Hope this helps
Factor out -1
-1(x^2+x-6)
Factor the inner trinomial
-1(x+3)(x-2)
Final answer: B
Answer: 6
Step-by-step explanation: or 9
Answer:
4/6 of a book in an hour
Step-by-step explanation:
1/6 = 1/4
1/4 x 4/1 = 1
1/6 x 4/1 = 4/6
Bam! UwU
Lol Hope This Helps !